Resisting Cyber-attacks in Digital Banking using Visual Cryptography - Prasanthi, B V; Bonthu, Sridevi (International Journal of Computer Sciences and Engineering, 2025)
With increasing demand of security, user authentication occupies prior in information security and plays a prominent role in protecting user's privacy, which has become a critical issue nowadays. In this digital world the usage of online transactions became very common and at the same time various attacks are performed behind this. The most common method used for authentication in online banking is by providing text password, which is the combination of letters, sequence of characters and special symbols. Authentication system, based on text passwords is widely used but they can easily compromise with attacks. Users normally select simple passwords because they can easily memorize at the time of login. So providing more security than existing assists in protecting resources against unauthorized access. Image-based-authentication is a good alternative to traditional password system. Apart from many conventional cryptographic methods, visual cryptographic techniques have also been used for providing security to data. In this proposed work, Visual cryptographic scheme is used that encrypts a secret image by breaking into image shares. Along with text based password login, image based authentication using visual cryptography is included. This authentication system is useful for various sectors like industries, online banking and shopping.